2014
DOI: 10.4103/1008-682x.127811
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary small-cell carcinoma: 11-year treatment experience

Abstract: The predictive factors of prognosis and treatment strategies for small-cell carcinoma (SCC) of the urinary tract are controversial. This study was aimed to investigate the clinical experience and management of patients with SCC of the urinary tract. We collected data of patients who were diagnosed with genitourinary SCC (GSCC) between 2002 and 2013 and were treated in the Fudan University Shanghai Cancer Center. A total of 18 patients were diagnosed with GSCC of which 10 originated from the prostate, seven fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…The major Gleason score was 8‐10, and nearly 70% of patients were accompanied by distant metastasis. In accordance with the present results, previous studies have demonstrated that prostate SCC was poorly differentiated, with high Gleason Score and widespread metastasis . What is surprising is that the distant metastasis rate from SEER database increased from 60.5% to 62% (reported by Deorah between 1973‐2003 and Wang J between 1973‐2004) to the 68% in this study (showed by our results between 2004 and 2015) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The major Gleason score was 8‐10, and nearly 70% of patients were accompanied by distant metastasis. In accordance with the present results, previous studies have demonstrated that prostate SCC was poorly differentiated, with high Gleason Score and widespread metastasis . What is surprising is that the distant metastasis rate from SEER database increased from 60.5% to 62% (reported by Deorah between 1973‐2003 and Wang J between 1973‐2004) to the 68% in this study (showed by our results between 2004 and 2015) .…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with the present results, previous studies have demonstrated that prostate SCC was poorly differentiated, with high Gleason Score and widespread metastasis. 1,2,[14][15][16] What is surprising is that the distant metastasis rate from SEER database increased from 60.5% to 62% (reported by Deorah between 1973-2003and Wang J between 1973-2004 to the 68% in this study (showed by our results between 2004 and 2015). 14,17 Additionally, we found that most patients showed normal serum PSA levels in contrast to other prostate carcinomas, and these results together with other studies showing prostate SCC patients without elevated PSA, may lead to missed diagnosis in these patients.…”
Section: Discussioncontrasting
confidence: 55%
“…To our knowledge, CS of small cell prostate carcinoma has rarely been described in association with high levels of plasma calcitonin [9]; recently CS and hypercalcitoninaemia have been reported in a small cell lung cancer [13]. Small cell carcinoma of the prostate is characterized by poor prognosis because it is quite often metastatic at the diagnosis [7, 14]. Generally PSA is not elevated, in particular in primary type [6], as probably occurring in the patient described.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate SCC is more likely to present with advanced disease when compared to bladder SCC. Not surprisingly, it also has a worse prognosis [ 31 ]. Tagawa, et al recently described a link between previously treated adenocarcinoma of the prostate and the development of neuroendocrine disease not responsive to androgen deprivation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As evident in the published literature, EPSCC carries a high risk of systemic relapse and multimodal therapy with cisplatin and etoposide chemotherapy appears to be the most widely accepted treatment modality [ 24 , 31 - 32 ]. Most studies recommend combination therapy centered on systemic platinum-based chemotherapy and local therapy with either radiation therapy or radical cystectomy [ 33 - 34 ].…”
Section: Discussionmentioning
confidence: 99%